Applications of laser radiation on cotton fabrics dyed gall oak(Quercus infectoria Olivier) - PARS, ABDULKADİR (My University, 2022)
In this study, at different ratios mordanted with iron (II) sulfate (FeSO₄.7H₂O) and potassium aluminum sulfate [KAl(SO₄)₂12.H₂O] cotton fabrics were dyed gall oak (Quercus infectoria Olivier). Laser radiation firstly was used on raw cotton fabrics and secondly, cotton fabrics with different ratios of metallic mordanted and dyed with gall oak were irradiated to examine the laser radiation effects on textile color using several combinations of the two main laser parameters namely the number of pulses and energy density at 1064 nm. Colorimetric analysis of the cotton fabrics was measured by CIEL*a*b* spectrophotometer and examined surface alterations. Morphological analysis was performed using optical microscopy

Bu çalışmada, farklı oranlarda potasyum alüminyum sülfat [KAl(SO₄)₂12.H₂O] ve demir sülfat (FeSO₄.7H₂O) metal tuzlarıyla mordanlanan pamuklu kumaşlara mazı gomalağı bitkisiyle (Quercus infectoria Olivier) doğal boyama işlemi yapılmıştır. 1064 nm’de lazer radyasyonun farklı puls sayısı ve enerji yoğunluğu kombinasyonları kullanılarak ilk olarak ham pamuklu kumaşlarda ve ikinci olarak, farklı oranlarda metalik mordanlanmış ve mazı gomalağı ile boyanmış pamuklu kumaşlarda ışınlama yapılarak renk üzerindeki etkileri incelenmiştir. Pamuklu kumaşların kolorimetrik analizi CIEL*a*b* spektrofotometre ile ölçülmüş ve pamuklu kumaşların yüzey değişimleri incelenmiştir. Morfolojik incelemelerd
Mazi meşesi̇ (quercus infectoria olivier) i̇le boyanmiş pamuklu kumaşlarda lazer radyasyon uygulamalari
Keywords: Pamuklu kumaş; Lazer radyasyonu; doğal boyalar; metalik mordanlar; CIEL*a*b*; Cotton fabric; Laser radiation; natural dyes; metallic mordants